Morphology and taxonomy of the South African species of the genus Margarodes (Hemiptera: Margarodidae), with detailed studies on the biology of two vine infesting species - De Klerk, Christiaan Andreas (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. Agric.) -- University of Stellenbosch, 1978.